Analisis kebijakan insentif pajak pada masa covid-19 yang melanda di Indonesia: PPh Pasal 25 dan PPh final - Hariadi, Dwi Sukma Jaya (Maliki Interdisciplinary Journal, 2024)
The tax sector is getting quite significant influence due to the covid19 pandemic that hit Indonesia. One of Indonesia's efforts to make it easier for taxpayers to pay taxes is to implement an intensive tax policy. This is attributed to various factors affecting the taxpayer in paying his tax bill. This study is a quantitative study and literature study whose data were collected through previous studies on tax-intensive policies. In addition, this study also used data on tax intensive policies during the covid19 pandemic related to PPh article 25 and PPh final. This study shows that PPh article 25 can be given to taxpayers matching the Business Field Classification (KLU). Meanwhile, the final PPh is aimed at the recipient contraction service of the program to accelerate the improvement of the irrigation water system (P3-TGAI) which is borne by the government.